2018
DOI: 10.4236/ojss.2018.85011
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Salinity Stress in Maize Seed Germination and Seedling Growth Attributes through Seed Priming

Abstract: Germination of seeds and growth of seedling respond to seed priming as priming can guard the damage of salinity stress. A study conducted in the net house of the Department of Agronomy, BAU, Mymensingh during the period from November 2012 to April 2013 investigated the ameliorative effect of seed priming on seed germination and seedling attributes of maize under various salinity stress conditions. The experiment consisted of five seed priming and four salinity levels (NaCl) and laid out in a Completely Randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…The commencement and rate of germination is delayed by salt stress during germination, which was the reason the control was found to record the highest germination speed compared to other primers (Farooq et al, 2015). The speed of germination as affected by primer and salinity levels aligned with the work of (Akter et al, 2018), who studied the effect of priming and salinity levels on maize using 5 seed priming and 4 salinity levels and observed that there was significant different in seed germination percentage due to seed priming treatments and various salinity stress levels. The effect of priming and salinity stress on germination was observed to be due to the prevention of water entry into the seed as a result of the decrease in the osmotic potential in the soil solution (El Sabagh et al, 2021).…”
Section: Speed Of Germinationmentioning
confidence: 57%
“…The commencement and rate of germination is delayed by salt stress during germination, which was the reason the control was found to record the highest germination speed compared to other primers (Farooq et al, 2015). The speed of germination as affected by primer and salinity levels aligned with the work of (Akter et al, 2018), who studied the effect of priming and salinity levels on maize using 5 seed priming and 4 salinity levels and observed that there was significant different in seed germination percentage due to seed priming treatments and various salinity stress levels. The effect of priming and salinity stress on germination was observed to be due to the prevention of water entry into the seed as a result of the decrease in the osmotic potential in the soil solution (El Sabagh et al, 2021).…”
Section: Speed Of Germinationmentioning
confidence: 57%
“…Seed priming techniques utilize different osmotic solutions as seed priming agents including inorganic salts, sugars, growth regulators and polyethylene glycol [111]. Broadly, there are two seed priming techniques, known as uncontrolled hydration or hydro-priming [112], and controlled hydration, which includes methods such as osmotic priming, solid matrix priming, and hormonal priming [113]. Among others, polyethylene glycol (PEG), chlorides, sulphates, nitrates, glycerol, sorbitol have also been commonly used as osmotic priming agents having germination enhancing effect for different cereals including maize [23].…”
Section: Seed Primingmentioning
confidence: 99%
“…Maize is regarded to be one of the cereals that is most salt-sensitive (Maas and Hoffman, 1977;Sabagh et al, 2021). Salinity is especially harmful to maize during germination and at the seedling growth stage (Akter et al, 2018). Like other abiotic stresses, salt stress in maize also leads to oxidative stress by the enhanced production of reactive oxygen species (ROS) (Shah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%